Political opposition in the Kingdom of Saudi Arabia 1948-1975 (historical study) (Journal of the College of Basic Education, 2019)
The subject of the political opposition in the Kingdom of Saudi Arabia is one of the topics in which the researcher faces many difficulties due to the strict concealment and opacity imposed by the authorities in the Kingdom of Saudi Arabia on any information related to the opposition. Rather, it prevents access to documents and publications that are distributed in some regions of the Kingdom, as well as the procedures Taken against opposition movements, the Kingdom of Saudi Arabia is a closed political system that prevents the spread of information about political unrest and opposition activities and suppresses attempts to uncover them.From this point of view, the research aims to reveal some aspects of this ambiguity and shed light on the political, social, and economic conditions under which the opposition movements, their trends, goals, and external connections have arisen, their level of influence in the Saudi political arena and their success in achieving their goals depending on the information, documents and reports available to the researcher. A secret related to the activity of opposition movements and the position of the Kingdom of Saudi Arabia on that activity. Over the past few years, some information has leaked out of the Kingdom indicating that a large number of disturbances and demonstrations were occurring among the ranks and neighborhoods of the middle and poor classes from time to time, whether in the military or civilian sectors. For a clearer and deeper understanding of the issue of the political opposition in the Kingdom of Saudi Arabia, it is necessary to first identify the historical and political context in which that opposition operated, its legitimacy, its role, the political programs it adopts, and the goals it seeks and struggles to achieve in a country where the formation of political parties is prohibited. Or any form of political groupings, which makes political work confined to a narrow scope and characterized by extremes of Fashion and secrecy, and often ends in a confrontation with the political system.